Kunglig skandal, kvinnlig skuld - Lignell,Beatrice; Johansson,Lisa (2026)
Abstract This qualitative study explores how Swedish evening newspapers Aftonbladet and Expressen reported on former prince Andrew Mountbatten Windsor during his scandal regarding allegations of sexual harassment and rape. Through thematic content analysis, using Liz Kelly’s (1988) feminist framework on violence as a continuum and Swedish conventional practices and rules regarding media ethics, this study provides an account of how the routinised news coverage on royal family members is modified while simultaneously reporting on a serious topic such as sexual violence. The analysis reveals three overarching themes throughout the news reporting by Aftonbladet and Expressen on Andrew Mountbatten Windsor: a displacement of responsibility from the former prince to people in his immediate surroundings, a hierarchical depiction of sexual violence by the newspapers, and a depoliticised representation of the events through a personalised and privatised framing of power. This study concludes that although these journalistic practises were largely justified by legal caution and prevailing Swedish approaches to media ethics, they nevertheless risk reproducing the political power structures and cultural norms which protect perpetrators of sexual violence and marginalise their victims. The study contributes to research on media representations of sexual violence by highlighting the tension between journalistic ethics, commercial driving forces, and feminist critique.
Keywords: Nyckelord: Skandaljournalistik; hovjournalistik; sexuellt våld; medieetik; feministisk medieteori; gestaltningsteori; tematisk innehållsanalys; Aftonbladet; Expressen